2021
DOI: 10.1021/acs.jafc.0c07342
|View full text |Cite
|
Sign up to set email alerts
|

Lauric Triglyceride Ameliorates High-Fat-Diet-Induced Obesity in Rats by Reducing Lipogenesis and Increasing Lipolysis and β-Oxidation

Abstract: Medium-chain triglycerides (MCTs) are found in limited foods. In these medium-chain oil resources, the abundance of lauric acid (LA) is the highest among medium-chain fatty acids (MCFAs), and its effects on lipid metabolism in obese rats have not been well-studied. This study aimed to determine the anti-obesity effects and mechanisms of lauric triglyceride (LT) in Sprague Dawley (SD) rats. LA and glycerin were used to synthesize LT, then LT was used to treat obese rats for 12 weeks. The results showed that LT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
(88 reference statements)
1
29
0
Order By: Relevance
“…Dyslipidemia typically seen in obesity includes hepatic overproduction of very low‐density lipoproteins and increased free fatty acid delivery (18). In order to assess the effects of CS on liver function, we analyzed genes related to lipogenesis (sterol regulatory element binding protein 1 [SREBP‐1c], SREBP‐2, acetyl‐coenzyme A carboxylase [ACC], and fatty acid synthase [FAS]), triacylglycerol storage in adipocytes (peroxisome proliferator‐activated receptor γ [PPARγ]), and lipolysis (lipoprotein lipase [LPL] (19,20). We found no significant differences in mRNA levels of FAS or ACC in the liver (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyslipidemia typically seen in obesity includes hepatic overproduction of very low‐density lipoproteins and increased free fatty acid delivery (18). In order to assess the effects of CS on liver function, we analyzed genes related to lipogenesis (sterol regulatory element binding protein 1 [SREBP‐1c], SREBP‐2, acetyl‐coenzyme A carboxylase [ACC], and fatty acid synthase [FAS]), triacylglycerol storage in adipocytes (peroxisome proliferator‐activated receptor γ [PPARγ]), and lipolysis (lipoprotein lipase [LPL] (19,20). We found no significant differences in mRNA levels of FAS or ACC in the liver (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Dyslipidemia typically seen in obesity includes hepatic overproduction of very low-density lipoproteins and increased free fatty acid delivery (18). In order to assess the effects of CS on liver function, (19,20). We found no significant differences in mRNA levels of FAS or ACC in the liver (Figure 5A).…”
Section: Liver Gene Expressionmentioning
confidence: 89%
“…These were in line with our previous research, showing that as the expression of CYP8B1 protein in the LT group decreased, the expression levels of lipogenesis-related genes and proteins also decreased. 20 LXR is another key regulator of cholesterol homeostasis. It has been reported that the activation of LXR increased the expression of ABCG5 and ABCG8, 51 and it also reduced the small intestinal uptake of sterols.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Lauric triglyceride was synthesized in our laboratory (the yield of LT is 90%, and the purity after purification is ≥99%, Figure S1). 20 The details of 39 bile acid (BA) standards are shown in Table S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation